Wintering phenology and site fidelity of European Robins (Erithacus rubecula) in an eastern Mediterranean wintering area (Aves: Passeriformes). Issue 1 (2nd January 2022) - Karaardıç, Hakan
Abstract : The European Robin ( Erithacus rubecula ) is a partial migrant in Central Europe and the Eastern Mediterranean known as a wintering area. Little is known about the behaviour in the winter. I assessed the wintering phenology by using capture-recapture methods in a coastal area in southern Turkey. Over three wintering seasons, 76 European Robins were captured with mist-nets. Ten of them were recaptured in the following wintering seasons and another after two seasons. Recaptures peaked in November (26.5%) and December (26.5%) and then declined progressively to February (14.7%). Our results suggest a high level of site fidelity in the wintering area in subsequent years.